Pengaruh Harga Dan Kualitas Pelayanan Terhadap Volume Penjualan Pada Pangsit Goreng Viral Tangerang Selatan - M. Deni mahendra; Jaenudin Jaenudin (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
The aim of this research is to determine the effect of price and service quality on sales volume at Viral Fried Dumplings in South Tangerang. The method used is a quantitative research method and uses a descriptive approach. The sampling technique used was probability sampling, a proportional stratified random sampling technique with sampling using the Slovin formula of 99 respondents. Data analysis uses simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination and hypothesis testing. The results of this research are that price has a positive and significant influence on sales volume. Service Quality has a positive and significant influence on Sales Volume. Price and Service Quality simultaneously have a positive and significant influence on Sales Volume. Price and service quality contributed to sales volume by 84.1%. The most dominant independent influence is service quality with a contribution of 67.5%. Meanwhile, price contributed 57.1%.